Tatbīq Al Ansyitah Al Lughawiyah Li Tanmiyah Al Syakhshiyah Al Wasatiyah Li Tullāb Ma’had Al Muhibbīn Tūbān - Aldzakhiroh, Nilna; Mustofa, Syaiful; Rusuly, Usfiyatur (STIQ Amuntai, 2025)
The latest worrying phenomenon in society is the increasing polarization and extremism, which affects the behavior of the younger generation, including among students. To counteract this negative influence, Al Muhibbin Islamic Boarding School in Tuban implements language activities. Al Muhibbin Islamic Boarding School in Tuban implements language activities as a strategy to foster moderate character. This study aims to analyze the implementation of language activities and their impact on fostering the moderate character of students. The method used is qualitative with a case study approach, involving observation, interviews, and document analysis. The results of the study indicate that Arabic speech fosters moderate character in students by promoting values of tolerance, nationalism, and anti-violence through practice and speech materials. Arabic debates, through the process of practice and debate themes, foster values of nationalism, tolerance, and anti-violence. Arabic carving fosters pride in local culture and a sense of love for the homeland through craftsmanship. Through practice and thematic exploration, Arabic drama can instill tolerance and nationalism in students. Strengthen a sense of pride in various regional specialties, which are a reflection of local culture and love for the homeland. Overall, language activities at Al Muhibbin Tuban Islamic Boarding School not only function as a means of improving language skills but also as a successful effort to form moderate characters, which are expected to contribute to society. The daily attitudes of students who respect each other are a testament to this.